How neighborhoods matter in fatal interactions between police and men of color. (January 2019) - Johnson, Odis; St. Vil, Christopher; Gilbert, Keon L.; Goodman, Melody; Johnson, Cassandra Arroyo
Abstract: This article addresses the concern that death by legal intervention is a health outcome disproportionately experienced by boys and men of color, and predicated on the quality of the locations in which encounters with law enforcement occur. Using a more comprehensive cross-verified sample of police homicides from online databases and a nationally representative sample of law enforcement agencies, this study examines whether neighborhood social disorganization, minority threat, and defense of inequality theories help explain the odds that males of color will have a fatal interaction with police (FIP). There are several noteworthy results. First, in support of the defense of inequality thesis, we found that income inequality within the area in which a FIP occurred is related to increased relative odds of fatal injury for males of color and Hispanic males. Second, consistent with the minority threat thesis, we found low levels of racial segregation dramatically reduced the odds of a FIP for Black males while higher levels of segregation increased the odds for Hispanic males. Third, Hispanic males were over 2.6 times as likely as others to be killed by officers from agencies with relatively higher percentages of Hispanic officers. We conclude the study with a discussion of its implications for research and policy. Highlights: Minority threat and defense of inequality theories inform FIPs for males of color. Income inequality heightens the chances of a police homicide for Hispanic males. Lowered racial segregation reduces the odds of fatal injury for Black males. Racial segregation increased the odds of a police homicide for Hispanic males. Percentage of Hispanic officers raises risks of fatal injury for Hispanic males.